Identification of Prospective Chemistry Teachers’ Misconceptions When Practicing Basic Teaching Skills and Their Correction Through Cognitive Conflict Strategies - Sri Winarni*; Syahrial Syahrial (Universitas Syiah Kuala, 2023)
Chemical misconceptions occur in almost all topics. Identification of chemical misconceptions has been carried out on students, students and even teachers. Chemical concepts are interrelated, so misconceptions at the primary level have the potential to cause misconceptions in the next concept. This study aims to identify misconceptions held by prospective chemistry teachers practicing basic teaching skills and overcome them through cognitive conflict strategies. This research is a naturalistic case study with an interpretive paradigm framework. Research is carried out naturally (natural setting) following the ongoing lecture program. The research was conducted during the even semester of the 2021/2022 academic year with 32 meetings for two classes. The research participants comprised 25 students (2 classes) taking microteaching courses. As the main instrument, the researcher is a microteaching subject with more than ten years of teaching experience. Data were collected using observation and interview methods with a cognitive conflict strategy framework. The results showed many misconceptions, including ionic bonds, ionization, and the formula for determining the pH of a buffer solution. Four prospective chemistry teachers experienced this misconception when practicing basic teaching skills. The correction results showed that 3 out of 4 students managed to correct the misconceptions that had been experienced before. One misconception is resistants. Based on the study results, it is recommended that a teacher or instructor pay attention to the misconceptions that occur and immediately overcome them as soon as possible.